Women and Customary Inheritance in Nigeria: A Critical Appraisal - Olufunmilola Adekiitan Omotayo (Matondang Journal, 2024)
This paper examines the inheritance and succession rights of women in Nigeria in relation to customary law. Using a critical appraisal approach, the study delves into the complexities and nuances of customary law and its impact on women's inheritance and succession rights. It analyses the various customary practices and cultural beliefs that affect women's rights to inheritance and succession. It provides a critical evaluation of the current practices and laws surrounding inheritance and succession rights for women in Nigeria. It reveals that the traditional inheritance system in Nigeria often favours male heirs and excludes women from inheriting properties or assets. This has resulted in persistent gender inequalities and discrimination against women in terms of land and property ownership. Furthermore, issues relating to succession in Nigeria are often based on customary practices and are largely patriarchal, which further exacerbates the issue of unequal inheritance rights for women. This poses a significant challenge to the empowerment and economic stability of women in Nigeria. The paper argues for the need for a shift in traditional and cultural practices that discriminate against women, hindering them from exercising their rights to inheritance and succession. It also suggests a need for legal and policy reforms that can promote gender equality and protect the rights of women in terms of inheritance and succession.